1993
DOI: 10.1016/0735-1097(93)90559-j
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the pattern of aortic root dilation in the Marfan syndrome

Abstract: The present study indicates that generalized aortic root dilation is a potent marker of an increased risk for subsequent aortic complications in Marfan syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
2
11

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(130 citation statements)
references
References 21 publications
11
106
2
11
Order By: Relevance
“…5,18,19 Increase in aortic diameter with age is usually invoked to explain progressively increasing prominence of the aortic knuckle in routine chest radiographs. Autopsy studies have shown a clear-cut increase in aortic surface area with age 20 (Figure 4), whereas cross-sectional studies of aortic diameter by angiography 21 and ultrasound [22][23][24][25][26] have shown lesser, but still definite, increase with age, except in the most proximal part of the ascending aorta. Gender differences are largely explicable on the basis of smaller body size in women.…”
Section: T He October 2004 High Blood Pressure Researchmentioning
confidence: 99%
“…5,18,19 Increase in aortic diameter with age is usually invoked to explain progressively increasing prominence of the aortic knuckle in routine chest radiographs. Autopsy studies have shown a clear-cut increase in aortic surface area with age 20 (Figure 4), whereas cross-sectional studies of aortic diameter by angiography 21 and ultrasound [22][23][24][25][26] have shown lesser, but still definite, increase with age, except in the most proximal part of the ascending aorta. Gender differences are largely explicable on the basis of smaller body size in women.…”
Section: T He October 2004 High Blood Pressure Researchmentioning
confidence: 99%
“…LV, left ventricle; LA, left atrium; Ao, aorta. After Roman et al 17 relatives), and in 66% (63% of probands, 67% of relatives) it could be unequivocally excluded. Ten patients from five families had FTAA, on the basis of a personal or family history or aortic root dilatation or dissection in the absence of other Marfan syndrome features.…”
Section: Evaluating the Use Of The Ghent Criteriamentioning
confidence: 99%
“…The cardiovascular assessment requires measurement of the aortic diameter at the Sinuses of Valsalva, usually by transthoracic echocardiography (Figure 4), and comparison with normal values based on age and body surface area, calculated from height and weight. 14,17 Other imaging techniques such as transoesophageal echocardiography or MRI scanning may be helpful in some cases. Assessment of the skeletal system should include pelvic X-ray to detect protrusion acetabulae, 18 if a positive finding would provide system involvement, or change skeletal system involvement to a major criterion, such that a positive Marfan diagnosis could then be made in conjunction with other system findings.…”
Section: In Briefmentioning
confidence: 99%
“…16, 19 MRI and computed tomography were not routinely used. The Japanese Circulation Society recommends an operation for patients with a sinus of Valsalva >5 cm (class IIa, level C) in all cases of Marfan syndrome.…”
Section: Measurement Of Aortic Diameter and Indication For Surgerymentioning
confidence: 99%